PENGARUH INOVASI, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA MINUMAN CHATIME DI KOTA DEPOK JAWA BARAT) - Muhammad Dzulqarnain (2021)
This research is quantitative and has the aim of knowing, proving, and analyzing the effect of innovation, promotion, and product quality on purchasing decisions for chatime drinks in the city of Depok, West Java. The population in this study are chatime consumers who have bought chatime drinks who are domiciled in the city of Depok, West Java. The sample collection method in this study is non-probability sampling and the type is purposive sampling. Sources of data obtained from the distribution of questionnaires to 100 respondents. To assist this research, the researcher uses a tool, namely the SmartPLS 3.3 analysis tool. The results obtained in this study are that innovation has a significant effect of 0.192 on purchasing decisions. Promotion has a significant effect of 0.284 on purchasing decisions. Product quality has a significant effect of 0.432 on purchasing decisions and the result of R Square Adjusted is 0.676 which means that the influence of innovation, promotion, and product quality variables on purchasing decisions is 67.6%. The limitation of this research is that it is still in the pandemic period, so the distribution of the questionnaire only uses Google forms.